Elongación del hipocótilo en plantas de frijol (phaseolus vulgaris) por tratamiento de embriones con mutágenos químicos y físicos. - Navarro Álvarez, Willy (1988)
Plants of common bean were selected with an elongated hipocotyle from M3 population produced through embryos treatment with EMS and gamma rays from Cobalt-60 source. The mutants with elongated hipocotyle were reproduced to know the inheritance of this character.